Positron Annihilation in Off‐Stoichiometric and Ta‐Doped Zn2TiO4. Issue 10 (8th August 2013) - Guagliardo, Paul R.; Vance, Eric R.; Lumpkin, Gregory R.; Blackford, Mark G.; Sudarshan, Kathi; Davis, Joel; Samarin, Sergey; Williams, James F.; Vanderah, T.
<x xml:space="preserve">Abstract</x> While Zn vacancies are regarded as the charge compensators in Ti‐rich Zn2TiO4, no evidence of cation vacancies in essentially single‐phase samples containing up to 13 wt% excess TiO2 was evident from positron annihilation lifetime spectroscopy (PALS). Nor was there strong evidence of cation vacancies in Ta‐doped samples targeted to contain either tetrahedral or octahedral vacancies, although there was a small increase in the lifetime as the doping level increased and the structure changed from cubic to tetragonal.